Comparative Study of Biogas Generations From Pineaple Peels and Spent Maize Grains Wastes and Their Ph-Parametric Correlations Using a Galvanized Iron Fixed-Dome Biodigester (Global Journal of Science Frontier Research, 2011)
Comparative study of biogas generations of pineapple peels (pp) and spent maize grains (SMG) wastes in terms of the pH-values using a constructed 0.459 m3 galvanized iron fixed-dome biodigester within 100 days retention period was carried out at Abakaliki area at 1:2.5 and 1:2 optimal ratio respectively.The measurements of the biogas volumes and pH values using the downward displacement techniques of water in a 25 litres calibrated white jerry can and the jean way 2020 pH-meter respectively were conducted at 9.30 am, 12.00 noon and 2.30 pm and the corresponding mean values computed for each day. Results showed peak values of 0.3378 litres at standard temperature and pressure (stp) at 22nd day (corresponding to 11.84 litres cumulation and 0.1518 litres at per day production rate) and 0.7814 litres at stp at 7th day (corresponding to 23.140 litres cumulation and 0.2822 litres at stp per day production rate ) respectively. Also the flammable biogas productions commenced on 12th day for pp-wastes and 8th day for SMG-wastes and their pH-value ranges are 5. 568-6.548 and 4.475-6.395.
Keywords: Biogas-volume; pH; digestion; regression-approximations